High prevalence of lower extremity peripheral artery disease in type 2 diabetes patients with proliferative diabetic retinopathy. - Yi-Wen Chen (PLoS ONE, 2015)
Little is known about the relationship between lower extremity peripheral arterial disease (PAD) and proliferative diabetic retinopathy (PDR) in type 2 diabetes (T2D). Here, we explored the relationship between sight-threatening PDR and PAD. We screened for diabetic retinopathy (DR) and PAD in hospitalized patients with T2D. Patients with a diabetic duration of more than 10 years, HbA1c ≥7.5%, eGFR ≥60 mL/min/1.73 m2 and with PDR or with no diabetic retinopathy (NDR) were eligible for this cross-sectional study. Severities of DR were graded by digital retinal photographs according to the Early Treatment Diabetic Retinopathy Study (ETDRS) scale. We assessed PAD by measuring Ankle Brachial Index (ABI), Toe Brachial Index (TBI) and Doppler ultrasound. Statistical analyses were performed using SPSS 17.0 software. Of the 1544 patients, 169 patients with extreme eye (57 PDR and 112 NDR) phenotypes met the inclusion criteria. Patients with PDR had a significantly higher proportion of low ABI (≤0.99) and high ABI (≥1.3) than patients with NDR (28.1% and 15.8% vs. 14.3% and 6.2% respectively, P<0.05). PDR patients also had lower TBI than NDR patients (0.56±0.09 vs. 0.61±0.08, P<0.01). The proportion of patients with abnormal duplex ultrasound was higher in PDR than in NDR (21.1% vs. 9.8%, P<0.001). This showed that PDR associated with PAD could be defined in multiple ways: abnormal ABI (≤0.9) (OR = 3.61, 95% CI: 1.15-11.26), abnormal TBI (OR = 2.84, 95% CI: 1.19-6.64), abnormal duplex (OR = 3.28, 95% CI: 1.00-10.71), and critical limb ischemia (OR = 5.52, 95% CI: 2.14-14.26). Moreover, PDR was a stronger independent correlation factor for PAD than a diabetic duration of 10 years. In conclusion, PAD is more common in PDR than in NDR. It implies that PDR and PAD are mostly concomitant in T2D. We should focus on screening PAD in patients with PDR in clinical practice.